"Fear Runs Deep:" The Anticipated Needs of LGBT Older Adults in Long-Term Care. Issue 8 (17th November 2018) - Putney, Jennifer M.; Keary, Sara; Hebert, Nicholas; Krinsky, Lisa; Halmo, Rebekah
ABSTRACT: Objectives: Older lesbian, gay, bisexual, and transgender (LGBT) adults are a vulnerable yet resilient population who face unique stressors as they foresee health decline. This paper presents the results of a study about community-dwelling LGBT older adults' anticipated needs and fears related to nursing homes and assisted living. Methods: This qualitative study collected data through seven focus groups. The sample ( N  = 50) consisted of LGBT-identified adults age 55 and over. We used an inductive, thematic analysis approach to data analysis. Results: Participants seek an inclusive environment where they will be safe and feel connected to a community. They fear dependence on healthcare providers, dementia, mistreatment, and isolation. Importantly, these fears can lead to identity concealment and psychological distress, including suicide ideation. Discussion: This study adds to the existing literature about the worries of older LGBT adults as they anticipate long-term care. The results suggest that older LGBT adults seek LGBT-inclusive residential care settings that encompass two distinct yet related aspects of LGBT-affirmative care: the procedural (e.g. culturally competent skills and knowledge of practitioners) and the implicit (e.g. the values and mission of the organization). This paper identifies implications for practice, policy, and training.